Uji Performa AAS Thermo Ice 3000 Terhadap Logam Cu Menggunakan CRM 500 dan CRM 697 Di UPT Laboratorium Terpadu UNS - S Sugito; Anang Kuncoro Rachmad Setiawan (UPT Laboratorium Terpadu, Universitas Diponegoro, 2022)
Atomic Absortion Spectrophotometer (AAS) or Atomic Absorption Spectrophotometer (AAS) is an instrument for analyzing metals, including: Pb, Cr, Ni, Cd, Fe, Zn, Cu, and Co where the basis of measurement is the measurement of light absorption by an atom. The unabsorbed light is transmitted and converted into a measurable electric beam. The purpose of this study was to determine the performance of the AAS Therma ICE 3000 tool on Cu metal testing using CRM 500 and CRM 697. This is very important because it greatly affects the validity of the measurement results in inorganic chemistry practicum activities, research and testing at the Chemical Laboratory of UPT Lab. Integrated UNS. Performance elements to be investigated include accuracy, precision, detection limit and linearity. From the results of the study, the results obtained accuracy <5% from control, repeatibility %CV count <2/3 CV Horwitz equation, detection limit with MDL 0.065 ppm and R2 for linearity of 0.9999